STUDENTS' CRITICAL THINKING PROCESS IN COMPETITION SCIENTIFIC WORKS - Hambali, Muhammad; Wahyuni, Lilik; Rizal, Maulfi Syaiful (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
Critical thinking processes are needed in solving problems. In this case, the critical thinking process consists of (1) recognizing the problem, (2) assessing relevant information, and (3) solving the problem/drawing conclusions. Based on this step, this research seeks to describe students' critical thinking processes in scientific work used by students to compete. The critical thinking process in competitive scientific work needs to be carried out so that students can create quality scientific work that is based on critical thinking in solving problems. This research uses a qualitative approach. This research data is in the form of sentences, sentence groups, paragraphs and complete texts which reflect students' critical thinking processes. Data was obtained from student scientific work that was competed outside campus. The research results show that in terms of the critical thinking process, students' scientific work can be categorized into four types, namely (1) scientific work which shows the three stages of the critical thinking process, namely the stages of recognizing problems, assessing relevant information, and solving problems/drawing out problems; (2) scientific work which only consists of the stage of recognizing problems and solving problems/drawing conclusions, (3) scientific work which consists of the stage of recognizing problems and assessing relevant information, and (4) scientific work which consists of the stage of recognizing information. Based on the research results, suggestions can be given to assist students in the critical thinking process so that scientific work is produced with in-depth and accurate discussion so that the scientific work written becomes quality scientific work for competition.